Obesity and osteoarthritis - analysis of relationships in patients undergoing primary hip arthroplasty - Misiło, Adriana; Sosna, Monika (Journal of Education, Health and Sport, 2023)
With attention to the increasing onset of disease, the number of typical diseases of old age is also increasing. Osteoarthritis is one of the most common diseases that affect elderly people. It forces to introduce various methods of treatment, support the improvement of the benefits and quality of life of patients. If the disease is severely advanced, an effective treatment is to replace the joint which is destroy. The results of the study is a retrospective analysis of patients who underwent hip arthroplasty in the first age of 2023.